TECHNOLOGY INTEGRATION IN LEARNING IN THE 21ST CENTURY EFL CLASSROOM IN INDONESIA - Bachtiar Bachtiar; Juhana Juhana; Aminudin Zuhairi; Lidwina Sri Ardiasih; Maya Puspitasari; Widya Rizky Pratiwi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This paper reports the outcomes of a ‘Community Service’ activity related to the integration of technology in English language teaching in Indonesia in the 21st century. The activity was conducted for junior high school English language teachers in Depok District, Indonesia. It outlines the opportunities and challenges faced by teachers in incorporating technology into their teaching and learning processes. Key themes emerging from the activity, include enhancing English language proficiency, increasing engagement and motivation, developing 21st-century skills, cultural exchange and global awareness, as well as the role of teachers and professional development. However, the effectiveness of technology integration heavily relies on the teachers' proficiency, availability of infrastructure, and pedagogical adaptation. The findings of the activity highlight the importance of comprehensive teacher training programs, improvements in educational infrastructure, and a pedagogical shift towards a curriculum more inclusive of technology. Recommendations include enhancing collaboration among stakeholders to support a technology-enriched learning environment to meet the evolving needs of learners in Indonesia.